Optimal Kiln Dry Allocation for Dry Timber Preparation to Minimize Cost - Juliet Theresia; I Gede Agus Widyadana; Didik Wahjudi (Jurnal Teknik Industri, 2019)
Optimization models are increasingly developed for planning and scheduling in manufacturing of natural resources. However, the uncertainty of material from natural resources makes it more difficult to develop a model.  In this paper, we concern about the cost of dry timber preparation for finishing process in a wood-board manufacturer. Based on characteristics of the material and wood-board production process, we develop two models to minimize transportation and drying cost of wood supply. The models consider the capacity of facilities, distances among facilities, and timber specification-based drying periods. The model is solved using linear programming, result in drying allocation of kiln dry’s chambers that gives the minimum cost of the process. A sensitivity analysis is conducted to demonstrate the effect of variation of internal capacity and external capacity to the objective function value. The results show that the total cost is more sensitive to the variation of the external capacity of kiln dry than the variation of the internal capacity.